1983
DOI: 10.1159/000123495
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-Induced Prolactin Release: Pharmacological Characterization of Receptors in Male Rats

Abstract: Studies were undertaken to investigate the nature of receptors involved in the prolactin-releasing action of histamine in male rats. The increase of plasma prolactin levels induced by third-ventricle injection of histamine was blocked by intraventricular injection of ranitidine, an H2-antagonist, but not by systemic administration of mepyramine, an H1-antagonist. The H2-histamine agonists 4-methylhistamine and Dimaprit, given intraventricularly in unrestrained and ether-anesthetized rats, enhanced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
(58 reference statements)
2
12
0
Order By: Relevance
“…The present study confirms that the PRL-releasing effect of histamine is exerted via H2-receptors following central infusion and via Hi-receptors following systemic infusion of the amine [9,15,16,19,32]. This pattern of receptor in volvement was still evident during serotonin blockade with methysergide or ketanserin.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present study confirms that the PRL-releasing effect of histamine is exerted via H2-receptors following central infusion and via Hi-receptors following systemic infusion of the amine [9,15,16,19,32]. This pattern of receptor in volvement was still evident during serotonin blockade with methysergide or ketanserin.…”
Section: Discussionsupporting
confidence: 85%
“…as well as systemic infusion [8,24]. The effect is mediated via ^-r e ceptors when histamine is infused centrally and via Hi-receptors when the amine is infused systemically [9,15,16,32], Following both administration routes the effect is ex erted at a suprapituitary site, presumably in the hypothala mus, since histamine has no direct effect at the pituitary level [16. 24.…”
mentioning
confidence: 99%
“…Moreover, when these drugs were injected into the lateral ventricles of the brain they did not increase blood prolactin (PRL) levels [II]. These results together with the reported data that H2 antagonists centrally administered, exert inhibitory influ ence on PRL release induced by histamine [3,15] suggest that cimetidine, in addition to its specific H2 antagonistic action, may exert other pharmacological effects responsible for PRL enhancement. Recently data have been published that demonstrate that cimetidine is able to inhibit the bind ing of benzodiazepines and y-aminobutyric acid (GABA) to brain receptors [8,19], This led us to investigate whether or not the GABA-ergic system is involved in the stimulatory effect of cimetidine on PRL secretion.…”
mentioning
confidence: 87%
“…It has previously been shown that histamine (HA) stimu lates prolactin (PRL) secretion dose dependently when in fused intracerebroventricularly or systemically (intra-arte rially) in male rats [8,15, 29] or in humans [17]. The stimu lation of PRL secretion following intracerebroventricular infusion of HA is mediated via Hi receptors, since the effect is blocked by Hi receptor antagonists and mimicked by H2 receptor agonists [8,15,16].…”
mentioning
confidence: 99%
“…The stimu lation of PRL secretion following intracerebroventricular infusion of HA is mediated via Hi receptors, since the effect is blocked by Hi receptor antagonists and mimicked by H2 receptor agonists [8,15,16]. In contrast, the stimulatory ef fect following intra-arterial infusion is mediated via Hi re-' Presented in part at the 14th Meeting of the European Hista mine Research Society, Aachen, FRG, May 1985, and at the 1st International Congress of Neuroendocrinology, San Francisco, Calif., USA, July 1986.…”
mentioning
confidence: 99%